Cycle-by-cycle variations in a direct injection hydrogen enriched compressed natural gas engine employing EGR at relative air-fuel ratios. - Olalekan, W.S. (EDP Sciences, 2014)
Since the pressure development in a combustion chamber is uniquely related to the combustion process, substantial variations in the combustion process on a cycle-by-cycle basis are occurring. To this end, an experimental study of cycle-by-cycle variation in a direct injection spark ignition engine fueled with natural gas-hydrogen blends combined with exhaust gas recirculation at relative air-fuel ratios was conducted. The impacts of relative air-fuel ratios (i.e. Î» = 1.0, 1.2, 1.3 and 1.4 which represent stoichiometric, moderately lean, lean and very lean mixtures respectively), hydrogen fractions and EGR rates were studied. The results showed that increasing the relative air-fuel ratio increases the COVIMEP. The behavior is more pronounced at the larger relative air-fuel ratios. More so, for a specified EGR rate; increasing the hydrogen fractions decreases the maximum COVIMEP value just as increasing in EGR rates increases the maximum COVIMEP value. (i.e. When percentage EGR rates is increased from 0 to 17 and 20 respectively. The maximum COVIMEP value increases from 6.25 to 6.56 and 8.30 respectively). Since the introduction of hydrogen gas reduces the cycle-by-cycle combustion variation in engine cylinder; thus it can be concluded that addition of hydrogen into direct injection compressed natural gas engine employing EGR at various relative air-fuel ratios is a viable approach to obtain an improved combustion quality which correspond to lower coefficient of variation in imep, (COVIMEP) in a direct injection compressed natural gas engine employing EGR at relative air-fuel ratios. Â© 2014 Owned by the authors, published by EDP Sciences.